Long term outcomes of strabismus surgery for third nerve palsy() - Merino, Pilar (J Optom, 2019)
PURPOSE: To report long-term outcomes of strabismus surgery for treatment of third nerve palsy. METHODS: We performed a 15-year retrospective study of patients who had undergone surgery. We analyzed preoperative mean deviation (at 6 months, 1 year after surgery, and at the end of follow-up), type of surgery, and factors predicting outcomes. A final deviation <10 prism diopters (pd) was considered a good esthetic outcome, and no diplopia in the primary position at the end of follow-up was considered a good functional outcome. RESULTS: Surgery was performed in 31 cases. Mean age was 36.27 years (women, 51.6%). Total and complete third nerve palsy was recorded in 22.6% and acquired palsy in 80.6%. Mean preoperative horizontal deviation (HD) in primary position was 40.24 pd (near) and 44.29 (distance) and 14.33 pd in vertical deviation (VD). Mean final HD was 8.94 pd (near) and 11.35 pd (distance), and mean final VD was 6.13. One surgery was performed in 68.9%. A favorable esthetic outcome was obtained in 64.5% and a successful functional outcome in 72.2%. Statistically significant differences were found between near HD (p = 0.019) and distance HD (p = 0.035) at 1 year compared with the end of follow-up and between VD at 6 months and 1 year after surgery (p = 0.03). Mean follow-up was 6.05 years. No specific factors predicted a successful outcome. CONCLUSIONS: Esthetic and functional results were similar. No predictors of successful outcome were identified. HD was better 1 year after surgery, and VD improved during follow-up.